The Transfer of Information as a Principle of Musical Creation: Between Data and Meaning (I) - ANDRONE-NAKANISHI, Sebastian (Studia Universitatis Babes-Bolyai Musica, 2025)
This study explores how information transfer shapes contemporary musical creation. It examines the dynamic relationship between composer, performer, and audience, emphasizing that music is not merely a technical process but a continuous exchange of meaning. The study highlights Gustav Mahler’s Symphony No. 1 and Rautavaara’s Cantus Arcticus as examples of reinterpretation and contextual transformation. It introduces the Informational Transfer Device (ITD) concept, illustrating how musical ideas evolve through multiple agents. The paper also addresses the ontological role of information in music, drawing on Aristotelian causality and modern information theory. Furthermore, it explores perception, interpretation, and cultural context in musical reception, comparing these mechanisms to the Kuleshov Effect in cinematography. Finally, the study offers practical applications for composers and performers, demonstrating how informational transfer principles can enhance expressivity, audience engagement, and interdisciplinary artistic collaborations.